Aesthetic experiences and their transformative power: a systematic review - Pizzolante, Marta; Pelowski, Matthew; Demmer, Theresa Rahel; Bartolotta, Sabrina; Sarcinella, Eleonora Diletta; Gaggioli, Andrea; Chirico, Alice (Frontiers in Psychology, 2024)
Background: Transformative experiences (TEs) have been conceptualized in many ways, contexts, magnitudes, and durations, but at their heart, they entail some manner of adjustment, which contributes to changing individuals' worldviews, actions, views of others and/or their own feelings, personality, and identity. Among the many elicitors identified as being able to foster TEs, an emerging body of literature has suggested that TEs might be prevalent in aesthetics or emerged from encounters with human art. Beyond denoting ordinary moments characterizing our daily lives, art and aesthetics could occasionally represent profound changes, causing shifts in our perceptions, beliefs and understanding of the world. However, in the realm of psychological inquiry, the extent to which art and aesthetics can be considered potential catalysts for transformation remains a topic of debate.Furthermore, a comprehensive identification of the key psychological components that contribute to the process of transformation before, during, and after aesthetic engagement is still missing.: This systematic review endeavors to address these gaps by synthesizing literature on aesthetic transformative experiences either from the field of psychology or explicitly delving into the psychological impact of transformative experiences within the realm of art and aesthetics. Methods: Two major electronic databases were systematically searched. The review was conducted in accordance with Liberati et al. (2009) and PRISMA guidelines. All stages of the review were conducted independently by three researchers, and the protocol was published on PROSPERO. Results: Although 39.440 studies were identified, only 23 peer-reviewed articles were included in this review, as most studies did not explicitly delve into the long-lasting psychological impact of art and aesthetics.The results confirm the potential of art and aesthetics as elicitors of transformation regardless of the type of artwork and the usage context. Moreover, it also identifies some psychological components necessary for transformation in the realm of art and aesthetics, including facilitating conditions/pre-expectations, cognitive discrepancy, epiphany and insight, and several after-effects on the recipient.The review aids in refining and enriching the concept of transformative experience, paving the way for further research and applications in various fields, including not only psychology but also education and therapeutic interventions.